Peranan perunding tanah dalam proses permohonan serah balik dan kurnia semula (SBKS) dalam negeri Johor - Ibrahim, Abu Bakar (2007)
Land development is a process of land planning is based on a proper and well infrastructure planning at a beginning stage. Developing of land needs a proper and rapid arrangement which some cases it consumed longer time and sometimes unpredictable. Therefore, this research which comprises of various application pertaining to land development such as Surrender and Realienation (SBKS), sub division of land and it is indeed involved with a various technical department. Besides time frame, there are much complaints from the land owner on bureaucracies happen during the process which is created by some department. In view of this problems, this research would focus mainly on finding the solution of solving the process , a thorough and quality analysis has been done and to enables us to overcome these problems, an agent or runner should be the best person to render their service to expedite the application with all the technical department involved. This agent or runner will have to create a pleasant working environment with the Land Surveyor in order for both parties to ensure a smooth flow of work process, hassle free and most of all to expedite the process involved during the application.